Evaluating the performance of material handling system using simulation - Lee, Tsu Xin (2013)
This thesis discusses about the performance of material handling system at rice packaging plant. The objectives of this thesis are to model the rice packaging processes, evaluate the performance of the process which include throughput and resource utilization and improve the process. Arena, is the simulation software applied to model and examine the performance of the system in this study. Resource allocation and machine layout are important factors that affect to the efficiency of the process. After modeling the processes in Arena, “what if analysis” strategy is implemented to enhance the whole system by doing model experimentation. Integrating of simulation and “what if analysis” provided a better model, achieved all the objectives of this study. We can see improvements in term of the processing time, work in progress, resource utilization and efficiency of the system at the end of the project. By using simulation, we can solve the industrial problems without elevate production cost.